EM-based poor slot update method for MIMO IDD receiver in fast time-varying channels - Kim, Minsung; Cho, Jehoon; Oh, Taewon (IET communications, 2018)
In this study, the authors propose an expectation-maximisation (EM)-based poor slot update method for multiple-input multiple-output (MIMO) iterative detection and decoding (IDD) receivers to increase their channel tracking capability in fast time-varying channels. The poor slots that trigger error propagation in a frame are selected, the channel state information is updated, and the updated recursive least squares channel tracking algorithm is executed. The accurate channel tracking capability of this new channel updating technique contributes to a 3 dB improvement in the bit error rate performance of an IDD receiver in a fast mobile environment ($\gt \!\!180\,km/h$>180km/h). The authors also demonstrate that an $\sim 20-25$∼20−25% complexity reduction can be achieved under various conditions.